The Challenge of Evaluating Participatory Budgets: Review of Models and Approach to a Synthetic Proposal - Esteban-Carbonell, Elisa; Romero-Martín, Sandra; Tomás-del Río, Eva María; Gómez-Quintero, Juan David (Revista del CLAD Reforma y Democracia, 2021)
Participatory budgets (PB) have become the most widespread mechanism in the framework of the construction of participatory democracies on a planetary scale. At the same time, although at a slower pace, there has been a proliferation of initiatives that seek to gauge the democratic quality of these public budgetary management processes. The diversity of experiences, the heterogeneity of socio-political contexts in which they are implemented, and their own evolution have generated a wide but confusing analytical repertoire for the evaluative practice of participatory budgets. Consequently, to adequately evaluate this mechanism of democratic deepening constitutes a challenge, in addition to an imperative for administrations and analysts. The ultimate aim of this paper is to formulate a proposal for a synthetic evaluation model that gathers and organizes this repertoire of works. The method involved a review of the existing evaluative models in the scientific literature by identifying the analytical axes included in each of the proposals. Based on this analysis, a proposal is formulated that integrates the results of the review and includes other emerging categories of analysis. The proposed model includes 105 indicators grouped into 35 areas, 15 criteria and 4 dimensions. The results provide significant innovations in two directions. On the one hand, in terms of the internal structure of the proposed model, a complete methodological sequence is incorporated that overcomes the fragmentation in terms of the levels of categorization of the previous inputs analyzed. On the other hand, in terms of its content, the model includes an area related to the deployment and development of the participatory process, which allows the incorporation of contingent variables that contribute to registering the dynamism of these experiences. Consequently, the indicators included in the model, in addition to being relevant, measurable and easy to apply, are sensitive to capture those aspects that can contribute to plan how to face the limitations detected and strengthen the potential of the different processes that are implemented. This model aims to contribute to the design of systematic evaluation procedures and could be used to evaluate future experiences.
Keywords: Budget; Participatory Budgeting; Citizen Participation; Evaluation Models; Administrative Indicators; Proposal